1997
DOI: 10.1080/01904169709365317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aluminum stress on shoot and root growth of contrasting genotypes of coleus

Abstract: Two cultivars of Coleus blumei Benth., found previously to differ in stress tolerance to UV-B radiation, water stress, and air pollutants-stress-tolerant 'Marty' ('M') and stress-sensitive 'Buckley Supreme' ('BS')-were grown in a greenhouse at Beltsville, MD in nutrient solutions containing 0 to 24 mg aluminum (Al) L -1 (Experiments I and II) and on an acid Al-toxic Tatum subsoil (clayey, mixed, thermic, Typic Hapludult) (Experiment III) at six lime levels, from 0 to 6,000 μg calcium carbonate (CaCO 3 ) g -1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They also indicated that most lines were sensitive to Al, but ninety lines showed intermediate tolerance. Krizek et al [124] tested two cultivars of Coleus blumei in nutrient solution containing 0 to 24 mg/l aluminium and on an acid Al-toxic Tatum subsoil under greenhouse conditions. Significant inhibitory effects of Al stress on shoot growth were generally observed in solution culture at 8 mg/l Al or higher concentration, while inhibition of root growth in solution culture was generally observed at 16 mg/l Al or higher levels.…”
Section: Existence Of Differential Tolerancementioning
confidence: 99%
“…They also indicated that most lines were sensitive to Al, but ninety lines showed intermediate tolerance. Krizek et al [124] tested two cultivars of Coleus blumei in nutrient solution containing 0 to 24 mg/l aluminium and on an acid Al-toxic Tatum subsoil under greenhouse conditions. Significant inhibitory effects of Al stress on shoot growth were generally observed in solution culture at 8 mg/l Al or higher concentration, while inhibition of root growth in solution culture was generally observed at 16 mg/l Al or higher levels.…”
Section: Existence Of Differential Tolerancementioning
confidence: 99%
“…For the first time, they demonstrated that Al tolerant group of wheat was able to increase pH in nutrient solutions comparatively to Al sensitive cultivars, when both are tested with or without Al. [82] tested two cultivars of Coleus blumei in nutrient solution containing 0 -24 mg/L Al and in Al-toxic tatum subsoil under greenhouse conditions. Inhibitory effects of Al-toxicity were observed on shoot growth, that were cultured in nutrient solution having Al concentration 8 mg or above, while inhibition of root growth was observed in solution having Al concentration 16 mg/L or above.…”
Section: Effect Of Aluminium On Shootmentioning
confidence: 99%